Identification of rice characteristics and quality in Sidenreng Rappang Regency - Rukmelia; Indrastuti; Husain, Salfiana; Nurwidah, Andi; Al Islamiyah, Syahmidarni (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2020)
Identification of the characteristics and quality of rice raises the case study of Sidenreng Rappang Regency. Sample is carried out in each District of Sidenreng Rappang Regency. The research aims to identify quantitatively the character of rice and to determine the quality classification of rice. The research was carried out by analyzing the water content of the sample, identification of head rice, broken grains, granular grains, red grains, yellow/damaged grains, calcifying grains, foreign objects and grain grains. The results showed that rice in Sidenreng Rappang Regency was 54.5% in accordance with the quality requirements of SNI 6128: 2015. While 45.5% of them do not meet quality standards. This shows that the quality of rice in Sidenreng Rappang Regency still needs to be improved, as well as maintaining the quality of rice that is in accordance with applicable quality standards.